The Influence of Perceived Value and Brand Experience on Purchasing Decisions of YouTube Premium Services (Study on Followers Instagram Account @Youtuber Karawang) - Anwar Musadad; Risha fatikha sari (LPPM Universitas Buddhi Dharma, 2023)
The study entitled